Schistosomus reflexus in a bovine fetus in Colombia: a case report - Gómez, César Augusto (2018)
A case of Schistosomus reflexus occurred in a cattle farm in Maní, Casanare, Colombia is reported. The reason for consultation was a cow with dystocia, who underwent obstetric examination by transvaginal palpation, reporting a malformation of the calf with exposure of abdominal viscera. A cesarean was performed and a dead calf with spinal inversion was extracted, the calf had incomplete closure of the abdominal ventral wall, exhibition of abdominal viscera and arthrogryposis, compatible with Schistosomus reflexus. This is the first reported case of this deformity in cattle in Colombia.